Evaluation of the cytogenetic aberration pattern in amyloid light chain amyloidosis as compared with monoclonal gammopathy of undetermined significance reveals common pathways of karyotypic instability - Bochtler, Tilmann; Hegenbart, Ute; Cremer, Friedrich Walter; Heiß, Christiane; Benner, Axel; Hose, Dirk; Moos, Marion; Bila, Jelena; Bartram, Claus R.; Ho, Anthony Dick; Goldschmidt, Hartmut; Jauch, Anna; et al. (Blood, 2008)
Chromosomal aberrations (CAs) have emerged as important pathogenetic and prognostic factors in plasma cell disorders. Using interphase fluorescence in situ hybridization (FISH) analysis, we evaluated CAs in a series of 75 patients with amyloid light chain amyloidosis (AL) as compared with 127 patients with monoclonal gammopathy of unknown significance (MGUS). We investigated IgH translocations t(11;14), t(4;14), and t(14;16) as well as gains of 1q21, 11q23, and 19q13 and deletions of 8p21, 13q14, and 17p13, detecting at least one CA in 89% of the patients. Translocation t(11;14) was the most frequent aberration in AL, with 47% versus 26% in MGUS (P = .03), and was strongly associated with the lack of an intact immunoglobulin (P < .001), thus contributing to the frequent light chain subtype in AL. Other frequent aberrations in AL included deletion of 13q14 and gain of 1q21, which were shared by MGUS at comparable frequencies. The progression to multiple myeloma (MM) stage I was paralleled by an increased frequency of gain of 1q21 (P = .001) in both groups. Similar branching patterns were observed in an oncogenetic tree model, indicating a common mechanism of underlying karyotypic instability in these plasma cell disorders.
Gesehen am 13.10.2021